Current practice of using the airway pressure release ventilation mode in acute respiratory distress syndrome patients among respiratory therapists in Saudi Arabia - Abdullah A Alqarni; Abdulelah M Aldhahir; Rayan A Siraj; Ahmed H Alasimi; Jaber S Alqahtani; Hassan Alwafi; Mohammed A Almeshari; Nowaf Y Alobaidi; Mansour S Majrshi; Saeed M Alghamdi; Mohammed M Alyami (SAGE Open Medicine)
Background: There is a limited data examining the practice of using the airway pressure release ventilation mode for patients with acute respiratory distress syndrome among respiratory therapists. Objectives: To evaluate the current practice and barriers when using airway pressure release ventilation mode in the management of patients with acute respiratory distress syndrome. Methods: A cross-sectional online survey was disseminated between November 2022 and April 2023 to respiratory therapists in Saudi Arabia. Descriptive statistics were used to analyze the respondents’ characteristics. Results: Overall, 802 respiratory therapists (male: 59.60%) completed the survey. Five hundred nineteen (64.71%) did not receive training on airway pressure release ventilation mode. Moreover, 325 (40.52%) and 391 (48.75%) did not know if airway pressure release ventilation was used at their hospitals and if the mode was managed via protocol with acute respiratory distress syndrome patients. Of the participants, 276 (34.41%) reported that plateau pressure should be used as a target when setting P-high initially, while 427 (53.24%) believed that the initial P-low should be equal to 0 cmH 2 O. Moreover, 468 (58.36%) believed that the initial T-high should be between 4 and 6 s, while 548 (68.33%) believed the initial T-low should be a set time (between 0.4 and 0.8) seconds. The most appropriate intervention to improve ventilation and oxygenation was to increase the P-high, which was reported by 370 (46.14%) and 326 (40.65%) respiratory therapists, respectively. Inadequate training was the most common barrier (678, 84.54%) to airway pressure release ventilation implementation. Conclusion: Airway pressure release ventilation management varies between respiratory therapists which may be due to inadequate training and the absence of protocols.